ANALISIS NILAI TAMBAH PRODUK OLAHAN MANGGA (Studi Kasus Pada Produk Mango Fruit Strips Frutivez) - Yuniar Dianti Fauziah; Elly Rasmikayati; Bobby Rachmat Saefudin (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Mango fruit is one of the seasonal fruit groups that have the potential to be processed into processed products. The processing process is one of solution when the selling price of fruit is low during the harvest season and a lot of the harvest is wasted because it is stored too long. Raw materials that have run into a change in value can be estimated how much their value is. So the purpose of this study is to describe the background of the formation of the processed mango fruit strips from Frutivez and to analyze the added value of these products. The research design used is to use a quantitative design of case studies with the interview method. Data analysis was carried out by using the added value analysis of the Hayami method. The results showed that in one production process the added value obtained by the product was IDR 5,000 / kg with a ratio of 11%, where every IDR 100 the value of the mango fruit strips product contained an added value of IDR 11.